ARE POLISH BANKS STABLE? A SYSTEMIC RISK ANALYSIS - Piotr Misztal; Marcin Łupiński (Polityki Europejskie, Finanse i Marketing)
The financial crisis that began in 2007 pointed out deficiencies in policy-makers’ responses to systemic risk. It turned out that not only individual bank insolvencies but also spillovers from negative externalities among entities can cause serious threats to the financial sector. During the last 10 years, many international and national initiatives were taken to strengthen the soundness of the financial system, introducing a macroprudential perspective to financial supervision. However, the recent COVID19 pandemic resulted in a serious negative shock for many economies and their financial sectors. In this paper, using the network model we try to analyse how these recent unexpected developments affected the Polish banking sector with systemic risk. To analyse Polish bank stability we developed a formal stress-testing framework based on the network model that allowed systemic risk identification, modelling and measurement. We tried to integrate analysis of time and the cross-sectional nature of systemic risk.